Chapter 38 Learning Analytics Approaches and cases from Asia - Hong, Huang- Yao (Taylor & Francis, 2018)
In this chapter, we present an overview of the field by articulating definitions and existing models of learning analytics. Case examples of learning analytics from Asian researchers are then summarized and reported. This is followed by an exploration of the key tensions in this field. The chapter concludes with a discussion of potential areas for future research in this area.